The making of black inks in an Arabic treatise by al-Qalalūsī dated from the 13th c. - Díaz Hidalgo, Rafael Javier (2023)
For the first time, this paper systematises the medieval preparation of black writing inks found in the important thirteenth century Andalusian technical treatise written by Muhammad ibn Idrīs ibn al-Qalalūsī (1210–1308). We present the Arabic version of this extraordinary text (‘The gifts of the wise men on the curiosities of the substances’), and its first English translation, as well as discuss key aspects of the processes that remain missing or are unclear indications. In this work, we studied the iron gall inks based on galls, where no other phenolic source is present. In this pedagogical treatise, the recipes for these black iron-gall inks are organised and classified by the gallnuts extraction method used: boiling (decoction), squeezing and infusion, with water being the only solvent used. The inks selected were reproduced and characterised through a multi-analytical approach. Quantification was performed by HPLC–DAD (high performance liquid chromatography with diode array detectors in the UV–VIS), showing that gallic acid is a minor compound in the gall extracts prepared following al-Qalalūsī instructions. In all the recipes, the higher concentration compounds in the gall extracts are the gallotannins pentagalloylglucose and hexagalloylglucose, ranging from 79 to 50% of the phenolic compounds. This supports the results of Raman and infrared spectroscopies. A comparison with medieval Iberian recipes was also done, which served to reinforce our previous results that show water as the sole solvent extracts with much lower yields than mixed solvents (water plus white wine or vinegar).